2018
DOI: 10.1016/j.celrep.2018.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Structure and Immune Antagonist Functions of Filoviral VP35 Homologs Present in Microbat Genomes

Abstract: Non-retroviral integrated RNA viral sequences (NIRVs) potentially encoding ∼280 amino acid homologs to filovirus VP35 proteins are present across the Myotis genus of bats. These are estimated to have been maintained for ∼18 million years, indicating their co-option. To address the reasons for co-option, 16 Myotis VP35s were characterized in comparison to VP35s from the extant filoviruses Ebola virus and Marburg virus, in which VP35s play critical roles in immune evasion and RNA synthesis. The Myotis VP35s demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 74 publications
(180 reference statements)
2
22
0
Order By: Relevance
“…Kondoh et al (2017) showed that exogenous expression of mEFL35 from M. lucifugus suppressed the antiviral signaling pathway in human cells. Edwards et al (2018) further expanded this finding. They used mEFL35 proteins from 16 Myotis species, and revealed that many of them showed similar activities in human and Myotis bat cells.…”
Section: Biological Functions Of Germline-integrated Riboviral Sequencesmentioning
confidence: 62%
See 2 more Smart Citations
“…Kondoh et al (2017) showed that exogenous expression of mEFL35 from M. lucifugus suppressed the antiviral signaling pathway in human cells. Edwards et al (2018) further expanded this finding. They used mEFL35 proteins from 16 Myotis species, and revealed that many of them showed similar activities in human and Myotis bat cells.…”
Section: Biological Functions Of Germline-integrated Riboviral Sequencesmentioning
confidence: 62%
“…EFL35 was probably integrated into the bat genome more than 20 MYA and retains a relatively long ORF, which has evolved and been maintained under natural selection (Belyi et al, 2010b;Katzourakis and Gifford, 2010;Taylor et al, 2010Taylor et al, , 2011. Kondoh et al (2017) and Edwards et al (2018) showed that EFL35 in Myotis bats (mEFL35) suppressed innate immune responses, as does the original protein VP35 of exogenous filoviruses. Kondoh et al (2017) showed that exogenous expression of mEFL35 from M. lucifugus suppressed the antiviral signaling pathway in human cells.…”
Section: Biological Functions Of Germline-integrated Riboviral Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…EBOV, MARV and LLOV VP35 have also been demonstrated to inhibit activation of PKR, an IFN-induced, dsRNA-activated protein kinase that exerts antiviral effects by suppressing translation (2124, 43). The mechanism by which VP35s inhibit PKR remains ambiguous, however, mutation of multiple central basic patch residues in EBOV or MARV VP35 disrupts the inhibitory activity (22, 23).…”
Section: Discussionmentioning
confidence: 99%
“…VP35 impairment of IFN-α/β production occurs by inhibition of RIG-I-like receptor (RLR) signaling through several mechanisms, including VP35 binding to RLR activating dsRNAs and the interaction of VP35 with PACT, a host protein that facilitates RIG-I activation (920). VP35s also inhibit the phosphorylation and activation of the IFN-induced kinase PKR (2124). EBOV VP24, but not MARV VP24, interacts with the NPI-1 subfamily of karyopherin alpha (KPNA) (also known as importin alpha) nuclear transport proteins, which includes KPNA1, KPNA5 and KPNA6 (25, 26).…”
Section: Introductionmentioning
confidence: 99%